2017
DOI: 10.1016/j.jsat.2016.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Long-term retention in Office Based Opioid Treatment with buprenorphine

Abstract: Background Guidelines recommend long-term treatment for opioid use disorder with buprenorphine; however, little is known about patients in long-term treatment. The aim of this study is to examine the prevalence and patient characteristics of long-term treatment retention (≥1 year) in an Office Based Opioid Treatment (OBOT) program with buprenorphine. Methods This is a retrospective cohort study of adults on buprenorphine from January 2002 to February 2014 in a large urban safety-net primary care OBOT program… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
138
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(154 citation statements)
references
References 37 publications
13
138
3
Order By: Relevance
“…To improve retention, consideration can also be given to inclusion of employment assistance, as some authors have suggested. [25] Acknowledgements. We acknowledge help from Tonya Esterhuizen (Centre for Evidence-based Health Care, Faculty of Medicine and Health Sciences, Stellenbosch University) with data analysis and the staff at the SBTC for assistance during data collection.…”
Section: Resultsmentioning
confidence: 99%
“…To improve retention, consideration can also be given to inclusion of employment assistance, as some authors have suggested. [25] Acknowledgements. We acknowledge help from Tonya Esterhuizen (Centre for Evidence-based Health Care, Faculty of Medicine and Health Sciences, Stellenbosch University) with data analysis and the staff at the SBTC for assistance during data collection.…”
Section: Resultsmentioning
confidence: 99%
“…A manual review of clinic notes was performed to identify patient-reported reasons for disengagement as part of a separate study. (Weinstein et al, 2017) Descriptive statistics were used to characterize the reasons for disengagement among the very early disengagers, which included broad categories such as health contraindications, insurance problems, clinic problems, and legal issues.…”
Section: Methodsmentioning
confidence: 99%
“…We selected race for use in the final model because previous studies have implicated racial disparities as a factor predicting substance use treatment outcomes. (Mennis & Stahler, 2015; Weinstein et al, 2017; Wells, Klap, Koike, & Sherbourne, 2001)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, longitudinal studies have demonstrated that individuals treated with pharmacologic agonist interventions such as methadone and buprenorphine effectively reduce opioid craving and use. 7,8 Detoxification without maintenance on one of these life-saving medications greatly increases the risk of overdose and death. 9,10 More recently, several studies have found that extended-release naltrexone (vivitrol) is equally effective as agonist treatments in reducing the risk of relapse once an individual is successfully inducted onto extended-release naltrexone.…”
mentioning
confidence: 99%